(untitled) (Research, Society and Development, 2021)
This work aimed to evaluate the influence of dry and wet heat processing on the antioxidant profile and antioxidant activity in ora-pro-nobis leaves. The leaves were collected, washed, and separated into three groups for the treatments: application of moist heat (hydrothermal cooking at 100 ºC / 4 minutes), application of dry heat (70 ºC / 8 hours), and control (raw material). The characteristics were evaluated: total soluble solids (SST), total solids (ST), pH, phenolic compounds (CPT), flavonoids (FT), anthocyanins (AT), antioxidant activity (AA). To identify the chemical profile and the chemical profile, fingerprints were obtained using PS / MS paper spray. The content of SST and ST decreased with moist heat. The CFT content increased with wet heat (12.43 ± 0.98) and decreased with dry heat (4.25 ± 0.93 g EAG 100 g-1). There was a decrease in the FT and AT content in the leaves processed with dry heat (132.67 ± 20.28 mg 100 g-1 and 19.70 ± 3.34 mg CG 100 g-1, respectively). AA decreased in both processes, which was higher in ora-pro-nobis leaves processed with dry heat (0.82 ± 0.0033 µmol ET g-1). 26 phenolic compounds were identified in the ora-pro-nob leaves by paper spray. The chemical profile, except for the substances 4,5-dimethyl-2,6-octadiene and methyl ester linolenic acid was not affected by thermal processing. Knowing the effect of food processing is important to understand the behavior of compounds that act beneficially on human health.